Experimental investigation on control of temperature asymmetry and nonuniformity in a pilot scale thermal flow reversal reactor. (5th July 2020) - Mao, Mingming; Shi, Junrui; Liu, Yongqi; Gao, Min; Chen, Qiang
Highlights: Temperature asymmetry and heterogeneity were investigated experimentally. The experiments were carried out on a pilot-scale thermal flow reversal reactor. Best switching time and methane concentration were validated for preheating process. The operation pattern with preheater off helped heat storage in the transition period. Minimum feed methane concentration of 0.2 vol.% could be identified. Higher feed methane concentration intensified temperature heterogeneity. The adjustment of valve opening ratio contributed to temperature uniformity. The adjustment of switching time ratio improved temperature symmetry. Synchronous adjustment of the two parameters accelerated the adjustment process. Abstract: Temperature asymmetry along flow direction and nonuniformity vertical to flow direction have been the prominent obstacles to the stable operation of thermal flow reversal reactor (TFRR) devices in industry. However, the relevant investigations are sorely lacking especially through the experiment method due to the limitation of laboratory test conditions. In this study, temperature asymmetry and nonuniformity for extra lean CH4 /air combustion (feed methane concentration below 1 vol%) in a pilot TFRR were investigated experimentally. The effects of the preheating process and feed methane concentration were investigated. The switching time of 120 s and feed rate of 400 m 3 /h were determined for the preheating process. In the transition period between preheating completion and cyclic steady state achievement, the operation pattern with preheater off was beneficial to heat storage. Stable combustion for minimum feed methane concentration of 0.2 vol% was confirmed in the experiment. When feed methane concentration was decreased from 0.8 vol% to 0.2 vol%, higher feed methane concentration was easier to intensify temperature nonuniformity. To restrain the increase of temperature asymmetry and nonuniformity, an electronically controlled adjustment was adopted. Valve opening ratio could be monitored to obtain more equivalent average temperature values of two sections of the packed bed. A 55-min process and a 116-min process were picked out from the cyclic steady-state period to eliminate temperature nonuniformity through adjusting valve opening ratio . As a result, the gaps in the high-temperature section width of two sections get narrowed and the average temperature of two sections is almost the same. The switching time ratio could be regulated to shift high-temperature cores of two sections to middle height position. A 58 min long process was selected with a switch time ratio of 1.25 and the temperature center height of both two sections dropped obviously. Synchronous adjustment of the valve opening ratio and the switching time ratio accelerated the adjustment process and double effects could be acquired in the meantime. A 36-min long process and a 28-min long process are chosen for simultaneous adjustment. The average temperature of two sections reach good agreement in the end and the temperature center height of two sections both drop obviously. This work is beneficial to the development of TFRR for better dealing with ventilation air methane and other lean gaseous fuel streams.